2019
DOI: 10.2478/remav-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modeling for Housing Renovation - Example for Ukraine

Abstract: Building Information Modelling (BIM) is the latest software technology used widely by many construction businesses - big and small - particularly within the Architecture Engineering Construction (AEC) sector. Besides being a design and documentation tool, building information models (BIM) provide a platform for enhanced knowledge base collaboration, the potential to manage modification, and therefore the capability to provide information support throughout the lifecycle of an apartment building. A big share of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It was also used to achieve restricted data redundancy, controlled unauthorized information access, transaction processing, integrity enforcement, and data recovery. It brought benefits for all types of construction related activities, be it facility management, existing building refurbishment, or maintenance works for operating building [2]. For a newly build project, it delivered the benefits for early awareness of conflicts in design stage, and scheduled monitoring along the construction period.…”
Section: Building Information Modellingmentioning
confidence: 99%
“…It was also used to achieve restricted data redundancy, controlled unauthorized information access, transaction processing, integrity enforcement, and data recovery. It brought benefits for all types of construction related activities, be it facility management, existing building refurbishment, or maintenance works for operating building [2]. For a newly build project, it delivered the benefits for early awareness of conflicts in design stage, and scheduled monitoring along the construction period.…”
Section: Building Information Modellingmentioning
confidence: 99%
“…The implementation of BIM in AEC projects in the last 10 years showed that the digitalization in construction environment has a significant impact on optimization of all the services and communication between all participants of an investment (Azhar, Khalfan & Maqsood, 2015). The application of BIM in Western European countries has been increasing and provides real savings of 20% in design and construction stages of AEC projects (Siniak, Źróbek, Nikolaiev & Shavrov, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This project highlighted the benefits of cost-oriented arrangements of construction activities in BIM technology. If the project is based on reliable information, project teamwork and decision-making BIM can facilitate design and renovation process by automated simulation of cost-activity information (Siniak et al, 2019).…”
Section: Bim Models For Renovation Projectsmentioning
confidence: 99%